Water saving strategies assessment on processing tomato cultivated in Mediterranean region - Marcella M. Giuliani; Giuseppe Gatta; Eugenio Nardella; Emanuele Tarantino (Italian Journal of Agronomy, 2016)
Processing tomato grown in Mediterranean region required high irrigation volume throughout growing season. A two-year study was carried out in order to investigate the effects of deficit irrigation (DI) and regulated deficit irrigation (RDI) on processing tomato cultivated under sub-arid conditions. A comparison between the irrigation management linked to common practice adopted by farmer and the irrigation management based on crop evapotranspiration (ETc) demand was also done. The tomato cv. Genius F1 was cultivated under five water regimes: minimal irrigation (I0), as irrigation only at transplanting and during fertilising; DI, to restore 60% ETc; RDI, to restore 60%-80%- 60% ETc across the three main tomato phenological stages; full irrigation (FI), to restore 100% ETc; and farmer irrigation (FaI), as irrigation following the subjective farmer method. Compared to FI, under the FaI regime, the seasonal irrigation volume was 31% and 26% higher in the 2009 and 2010, respectively, with not significant yield increase between the two water regimes. Among the irrigation regimes, only the RDI showed similar yield values over the two years, although 2010 was climatically less favourable. For the water use efficiency related to the marketable yield (WUEy), among the irrigation regimes, RDI showed the higher value together with FI. Finally, the Ky was 0.91, which indicates moderate water stress tolerance for processing tomato cultivated in Mediterranean regions. In conclusion, the data obtained in the present study demonstrate that in Southern Italy the irrigation planning followed by the farmer does not follow the principles of sustainable irrigation. Moreover, with the adoption of the RDI strategy, it is possible to save about 27% of water maintaining high WUEy value with an increase of fruit quality. The adoption of this regime could be suggested in processing tomato cultivated under Mediterranean climate saving water in both the vegetative and ripening periods.